Sodium Alginate Hydrogel Infusion of Bone Marrow Mesenchymal Stem Cell‐Derived Extracellular Vesicles and p38α Antagonistic Peptides in Myocardial Infarction Fibrosis Mitigation - Siyao Chen; Xiaodong Zeng; Meifeng Wu; Jiade Zhu; Yijin Wu (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Myocardial fibrosis is a pathological hallmark of heart failure post infarction, emphasizing the need for innovative treatment strategies. This research assesses the antifibrotic potential of a sodium alginate (SA) hydrogel loaded with extracellular vesicles (EVs) from bone marrow mesenchymal stem cells and PAP (p38α antagonistic peptides), aiming to interfere with fibrosis‐inducing pathways in myocardial tissue after infarction. Methods We induced fibrosis in mouse cardiac fibroblasts through hypoxia and disrupted the Mapk14 gene to study its contribution to fibrosis. Mesenchymal stem cell‐derived EVs, loaded with PAP, were encapsulated in the SA hydrogel (EVs‐PAP@SA). The formulation was tested in vitro for its effect on fibrotic marker expression and cell behavior, and in vivo in a murine model of myocardial infarction for its therapeutic efficacy. Results Map k14 silencing showed a decrease in the fibrotic response of cardiac fibroblasts. Treatment with the EVs‐PAP@SA hydrogel notably reduced profibrotic signaling, increased cell proliferation and migration, and lowered apoptosis rates. The in vivo treatment with the hydrogel post myocardial infarction significantly diminished myocardial fibrosis and improved cardiac performance. Conclusions The study endorses the SA hydrogel as an effective vehicle for delivering mesenchymal stem cell‐derived EVs and PAP to the heart post myocardial infarction, providing a novel approach for modulating myocardial fibrosis and promoting cardiac healing.